5 Multiple myeloma flow cytometry panel validated for clinical monitoring of patients. (9th November 2020) - Gang, Bevan; Sgouroudis, Vicky; Litwin, Virginia; Boyapati, Anita
Abstract : Background: Multiple myeloma (MM) is an incurable plasma cell malignancy with significant heterogeneity in clinical presentation. Plasma cells are antibody-producing cells of lymphoid origin that are resident in secondary lymphoid organs and in the bone marrow (BM). The detection of circulating malignant plasma cells using flow cytometry has also been described in patients with MM. Enumerating and phenotyping malignant plasma cells in the BM and peripheral blood (PB) may be of value when evaluating the presence of MM antigens targeted by therapies before and during treatment and at relapse. To this end, a flow cytometric panel was developed to enumerate and characterize malignant plasma cells and additional immune subsets. Methods: PB and BM aspirates (BMA) were obtained from healthy donors and MM donors who consented to research testing. MM cell lines were also used to spike into donor samples to detect specific antigens (collected in Cyto-Chex® blood collection tubes). Samples were then transferred to TruCount tubes to enumerate immune populations. Fluorescently labeled antibodies directed against CD38, CD138, CD56, CD45, BCMA were evaluated to assess parameters such as time and temperature stability of the reportable immune populations by monitoring the frequencies of the populations. In addition, the limit of quantitation, intra- and inter-assay precision were determined. Results: The MM Counting Panel was optimized to leverage antigen expression and fluorophore combinations. A gating strategy enabled enumeration of MM cells based on antigens that can be further subdivided based on BCMA expression. Further testing showed that the precision in frequencies and absolute counts of key reportable populations was deemed acceptable (%CV of <30%). The precision was within the acceptance criteria of%CV <30% for populations with =100 cells. Stability testing revealed that samples were more stable at ambient temperature relative to 4oC, with stability being maintained for 48 h post-collection, where at least 85% of reportable immune readouts were stable (%change <30% relative to baseline), for BMA and PB from various donors (healthy and MM).The panel was ultimately deployed for use with clinical samples from MM clinical trials. Clinical data generated from the MM Counting Panel allowed the identification of malignant plasma cell populations in BMA of patients from trial assessing a BCMAxCD3 bi-specific antibody (NCT03761108 ). Conclusions: A flow cytometric assay to enumerate and identify normal and malignant plasma cells in MM patients was successfully developed. The approach used can be applied to develop assays for other indications in which patients are treated with therapies.